(3XGgQI GdYhdeIs (3GdChgGe hGdMbGFbs - (3eSYO(B, (3eMj eMeOs ((3GdGScfOQjIs (3OGQ GdeWHhYGJ GdLGeYjIs, 2004)
(3eaGgje heQJcRGJ CSGSjI,LZQGajG GbJUGO GdeYdheGJ,KhQI GdeYdheGJ hfJGFLgG GdeLJeYjI,OhdfI GdEbJUGO hGdhWfjI GdEbJUGOjI,OhQ GdTQcGJ eJYOOI GdLfSjI aj XGgQI GdYhdeI,OhQ GdJWhQ GdJcfhdhLj aj XGgQI GdYhdeI,OhQ GdhWfjI GdEbJUGOjI aj YUQ GdYhdeI,GdKbGaI GdchfjI hGdNUhUjI GdKbGajI,JGQjN GdCacGQ GdEfSGfjI,GdMhGQGJ GdacQjI Mhd GdghjI GdKbGajI,YGdejI GdGSdGe cOYGeI CSGSjI ddKbGaI GdEfSGfjIs
Keywords: (3GdYhdeIs